2008
DOI: 10.1037/a0013355
|View full text |Cite
|
Sign up to set email alerts
|

Learning rule-described and non-rule-described categories: A comparison of children and adults.

Abstract: Three experiments investigated the ability of 3-, 5-, and 8-year-old children as well as adults to learn sets of perceptual categories. Adults and children performed comparably on categories that could be learned by either a single-dimensional rule or by associative learning mechanisms. However, children showed poorer performance relative to adults in learning categories defined by a disjunctive rule and categories that were nonlinearly separable. Increasing the task demands for adults resulted in child-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
143
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(177 citation statements)
references
References 48 publications
(156 reference statements)
26
143
1
Order By: Relevance
“…Lieberman et al, 2004). According to the COVIS model, for the hypothesis-testing system to operate, an intact/developed prefrontal cortex is required (Minda et al, 2008). TBI typically results in localized and diffuse prefrontal cortex damage and it was confirmed that all TBI patients in this study had suffered contusional injury to the prefrontal cortex and exhibited problems in executive functioning.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Lieberman et al, 2004). According to the COVIS model, for the hypothesis-testing system to operate, an intact/developed prefrontal cortex is required (Minda et al, 2008). TBI typically results in localized and diffuse prefrontal cortex damage and it was confirmed that all TBI patients in this study had suffered contusional injury to the prefrontal cortex and exhibited problems in executive functioning.…”
Section: Discussionsupporting
confidence: 65%
“…Note that other AGL researchers have employed patient populations, but never before has a TBI sample been used in the context of AGL or the implicit-explicit distinction (Knowlton & Squire, 1994Smith & McDowall, 2005. Also, note that results from Minda et al (2008) support the conclusion that a deficit in the prefrontal cortex impairs the function of the hypothesis-testing system. In Minda et al's study, children were impaired, relative to adults, in a categorization task which required the explicit development of complex rules, a finding which was explained in terms of the fact that the prefrontal cortex develops later than other areas.…”
Section: Introductionmentioning
confidence: 97%
“…For example, COVIS predicts that learning of an overall similarity category structure is less affected by time pressure or concurrent load than learning of a singledimension category structure (Minda et al, 2008;Waldron & Ashby, 2001;Zeithamova & Maddox, 2006). 6…”
Section: Differentiation Theorymentioning
confidence: 99%
“…Kemler, 1983;Minda, Desroches & Church, 2008). COVIS (see Ashby et al, 1998) and a variant of GCM (Smith, 1989) has been applied to a subset of these data, SUSTAIN to a different subset .…”
Section: Defining Domains Through Ivsmentioning
confidence: 99%